Pengaruh Terapi Brain Gym terhadap Peningkatan Perkembangan Motorik Kasar Anak Usia Prasekolah di Wilayah Puskesmas Gunungpati Kota Semarang - Erni Suprapti; Yuni Astuti (Lembaga Pengembangan Kinerja Dosen, 2023)
Children are an invaluable national asset. Children are part of the young population who need to be cared for, so that they can grow and develop optimally according to their potential. Motor development is an element of maturity in controlling body movements and the brain as the center of movement. Children's motor development can be assessed using the KPSP (Pre-Developmental Screening Questionnaire) which is an early detection instrument in the development of children aged 0 to 6 years. Gross motor skills are physical movements that require balance and coordination between body parts using the large muscles of some or all of the body parts. Gross motor development needs to be stimulated so that children can develop optimally. The aim of this research is to determine the effect of Brain Gym therapy on the gross motor development of preschool children. The design of this research is to use a Quasy experiment with a one group pre test-post test design. pre – post test. The total sample was 16 respondents with a purposive sampling model. The results of this research show that there is an effect of Brain Gym therapy on increasing gross motor development in preschool children with a p value of 0.001. The conclusion of this research is that there is an increase in gross motor development after implementing Brain Gym therapy in preschool children. Parents are advised to carry out this brain gym therapy at home to further optimize their child's development, especially gross motor development.